Multiple aPDT sessions on periodontitis in rats treated with chemotherapy: histomorphometrical, immunohistochemical, immunological and microbiological analyses - Longo, Mariéllen [UNESP]; Gouveia Garcia, Valdir [UNESP]; Ervolino, Edilson [UNESP]; Ferro Alves, Márcio Luiz [UNESP]; Duque, Cristiane [UNESP]; Wainwright, Mark; Theodoro, Letícia Helena [UNESP] (Elsevier, 2019)
Background: The aim of this study was to evaluate the effect of multiple sessions of antimicrobial photodynamic therapy (aPDT) on the treatment of experimental periodontitis (EP) in rats treated with chemotherapy. Methods: Chemotherapy using 5-fluorouracil (5-FU) consisted of intraperitoneal administration of 60 and 40 mg/kg of 5-FU. 120 rats were subjected to chemotherapy with 5-FU and divided into groups: PT (periodontal treatment); PT+1aPDT (PT and single aPDT session); PT+4aPDT(PT and 4 sessions of aPDT); 1aPDT (single aPDT session); 4aPDT(4 sessions of aPDT). EP was induced in the mandibular molars via ligature placement. The alveolar bone loss (ABL) area in the furcation region was analysed histometrically. Proliferating cell nuclear antigen (PCNA), tartrate-resistant acid phosphatase (TRAP), receptor activator of nuclear factor kappa-B ligand (RANKL), osteoprotegerin (OPG) and cleaved caspase-3 (CC3) were analysed by immunohistochemistry. Prostaglandin E2 was quantified using an ELISA, tumor necrosis factor (TNF)-α and interleukin (IL)-6 were assessed using a multiplex method. The prevalence of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Prevotella nigrescens, Prevotella intermedia and Fusobacterium nucleatum was assessed using PCR. The data were statistically analysed (P < 0.05). Results: The PT+4aPDT group showed lower ABL than the PT or 1aPDT groups on day 7. Rats treated with aPDT showed a higher number of PCNA-positive cells with reduced immunolabeling of RANKL. Significant reductions in Prevotella nigrescens were observed in the PT+4aPDT group and in Aggregatibacter actinomycetemcomitans for the 1aPDT and 4aPDT groups. Conclusion: Repeated sessions of aPDT as an adjunct or alternative therapy were effective at reducing ABL, regulating bone metabolism, and reducing Prevotella nigrescens and Aggregatibacter actinomycetemcomitans.
Keywords: Alveolar bone loss; Chemotherapy; Periodontitis; Photochemotherapy; Rats